{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Lesson 2 Solutions

# Lesson 2 Solutions - Notation log a x = log a x ln x = log...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Notation log a x = log a ( x ) ln x = log e ( x ) lg x = log 10 ( x ) lb x = log 2 ( x ) Note: If there is a problem written log x , assume that the base is not required to awnser the question (It will cancel out-Please check with me if it doesn’t). Rules for Logarithms log a ( xy ) = log a ( x ) + log a ( y ) log a x y = log a ( x )- log a ( y ) log a ( x y ) = y log a ( x ) log a ( a x ) = a log a ( x ) = x log a (1) = 0 log a ( x ) = 1 log x ( a ) log a ( x ) log a ( y ) = log y ( x ) log a b ( x y ) = y b log a ( b ) WARNING: In log a b , both a AND b must be positive. Also log a (1) = 0 means that log 1 ( a ) is undefined and log 1 (1) is multi-valued. Problem Set 1. Solve for x : log (8) = x log (4) log (8) = x log (4) log (2 3 ) = x log (2 2 ) 3log (2) = 2 x log (2) 3 = 2 x x = 3 2 2. Solve for x ( x > 1): log 3 ( √ x- 1) + log 3 ( √ x + 1) = 2 log 3 ( √ x- 1) + log 3 ( √ x + 1) = 2 log 3 (( √ x- 1)( √ x + 1)) = 2 ( √ x- 1)( √ x + 1) = 3 2 3. What is the sum of the following series?3....
View Full Document

{[ snackBarMessage ]}

### Page1 / 5

Lesson 2 Solutions - Notation log a x = log a x ln x = log...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online